Esophageal tuberculosis with coexisting opportunistic infections in a renal allograft transplant recipient. Issue 1 (February 2017) - Kumar, Sunil; Minz, Mukut; Sinha, Saroj K.; Vaiphei, Kim; Sharma, Ashish; Singh, Sarbpreet; Kenwar, Deepesh B.
Abstract: We report a renal allograft transplant recipient with esophageal tuberculosis (TB) coinfected with herpes simplex virus (HSV) and Candida . The patient presented with oropharyngeal candidiasis and was started on fluconazole. Upper gastrointestinal endoscopy showed whitish patches with mucosal ulcers in the esophagus. Histopathological examination confirmed TB and HSV infection. The patient recovered after antiviral, antifungal, and anti‐tubercular therapy with reduction in immunosuppression. In a TB‐endemic zone, TB can coexist with opportunistic infections in an immunocompromised host.